Philosophical Pedagogy of S. Šalkauskis - Paulauskas, Rolandas (Acta Paedagogica Vilnensia, 1991)
The paper outlines the main features of the philosophy of Stasys Šalkauskis, and deals with the connections between philosophy and education. It follows the professor’s the idea that pedagogy is practically adapted philosophy. Šalkauskis "system of complete education” springs from philosophy. This system distinguishes the basic functions of education (nurture, guardianship, training, tutoring), areas of education (physical, cultural, religious), principles of education (universality, harmony and subordination), levels of education (individual, social, national, international), etc. The article also discusses the actors and factors of education that are divided by Šalkauskis into the natural - who are “called by nature”, and appointed – who are “called by appointment”. To the former belong the family, the state and the Church, to the latter – educational institutions and youth organizations. The article explores Šalkauskis’ conception of national education. Although this conception emphasized patriotic education, special links to national culture, it also emphasized the importance of internationalization. International education complements the national education, gives it a higher sense of quality and value.
Keywords: philosophy of education; Šalkauskis; education system; national education; international education